PARAMEDIC VERBAL VIOLENCE AGAINST POS-COVID 19 PATIENTS AT THE TANETE PUBLIC HEALTH CENTER BULUKUMPA DISTRIK BULUKUMBA REGENCY: PRAGMAIC STRUKTURE - Syarifuddin Tundreng; Supriadi Supriadi; Kaharuddin Kaharuddin (Sean Institute, 2023)
The spread of the Covid 19 virus has been completed, but some paramedics still have the habit of speaking arrogantly and disrespectfully in serving patients. Paramedics at the puskesmas are responsible for helping patients recover from their illness. They should provide services with language and actions that guarantee the patient's feelings. This study aims to describe the verbal arrogance of some paramedics in serving patients at the Tanete Public Health Center, Bulukumpa District, Bulukumba Regency. Describe the patient's acceptance or response to verbal arrogance carried out by paramedics towards patients at the Tanete Health Center, Bulukumpa District, Bulukumba Regency. This research is included in the field research category. The object of data collection from paramedics. The data collection method is observation by recording, recording, and interviewing. The population was determined in the form of forms of verbal arrogance by paramedics in serving patients at the Tanete Health Center, Bulukumpa District, Bulukumba Regency and the patient's acceptance or response to forms of verbal arrogance at the Tanete Health Center, Bulukumpa District, Bulukumba Regency. The research sample was determined based on the amount of data required. Data analysis was carried out in a qualitative descriptive manner. The results showed that the forms of paramedic verbal arrogance towards patients were direct orders, and orders with a high intonation voice, orders to wait for services with a rather long duration. The three forms of verbal speech are determined based on the patient's acceptance or response when receiving paramedical services. The results of the patient's acceptance or response were: complaining, regretting, disappointed, angry, and raging.